COMMUNICATION PATTERNS OF WAYANG GOLEK PUPPETEERS IN PROVIDING SOCIAL CRITICISM MESSAGES TO THEIR AUDIENCES IN BANDUNG REGENCY - Irawaty, Sandra; Cunanda, Andriansyah; Kristin, Fie Lien (PT Altin Riset Publishing, 2024)
This study aims to investigate the communication patterns of wayang golek puppeteers in Bandung Regency as they deliver social criticism messages to their audiences. The primary objective is to understand how traditional wayang golek performances can address contemporary social issues while engaging audiences in meaningful dialogue. Employing a qualitative research methodology, this study utilized direct observations and in-depth interviews with key participants, including wayang golek puppeteers and audience members. The data collection involved attending live performances, analyzing the content and delivery of social critiques, and conducting interviews to gain insights into the effectiveness and reception of these performances. The findings reveal that Wayang Golek puppeteers employ interactive techniques to engage their audiences, incorporating contemporary issues into traditional narratives to provoke thought and reflection. The performances demonstrate a successful adaptation of cultural practices to address modern societal challenges, fostering a participatory dialogue between the puppeteers and their audiences. The study highlights the role of cultural symbols and allegories in bridging traditional values with contemporary social critiques and underscores the importance of maintaining cultural heritage while addressing current issues. The results contribute to the broader discourse on participatory communication and the role of traditional art forms in societal change.